Stat3 is a positive regulator of gap junctional intercellular communication in cultured, human lung carcinoma cells - Geletu Mulu; Arulanandam Rozanne; Greer Samantha; Trotman-Grant Aaron; Tomai Evangelia; Raptis Leda (BMC Cancer, 2012)
Abstract Background Neoplastic transformation of cultured cells by a number of oncogenes such as src suppresses gap junctional, intercellular communication (GJIC); however, the role of Src and its effector Signal transducer and activator of transcription-3 (Stat3) upon GJIC in non small cell lung cancer (NSCLC) has not been defined. Immunohistochemical analysis revealed high Src activity in NSCLC biopsy samples compared to normal tissues. Here we explored the potential effect of Src and Stat3 upon GJIC, by assessing the levels of tyr418-phosphorylated Src and tyr705-phosphorylated Stat3, respectively, in a panel of NSCLC cell lines. Methods Gap junctional communication was examined by electroporating the fluorescent dye Lucifer yellow into cells grown on a transparent electrode, followed by observation of the migration of the dye to the adjacent, non-electroporated cells under fluorescence illumination. Results An inverse relationship between Src activity levels and GJIC was noted; in five lines with high Src activity GJIC was absent, while two lines with extensive GJIC (QU-DB and SK-LuCi6) had low Src levels, similar to a non-transformed, immortalised lung epithelial cell line. Interestingly, examination of the mechanism indicated that Stat3 inhibition in any of the NSCLC lines expressing high endogenous Src activity levels, or in cells where Src was exogenously transduced, did not restore GJIC. On the contrary, Stat3 downregulation in immortalised lung epithelial cells or in the NSCLC lines displaying extensive GJIC actually suppressed junctional permeability. Conclusions Our findings demonstrate that although Stat3 is generally growth promoting and in an activated form it can act as an oncogene, it is actually required for gap junctional communication both in nontransformed lung epithelial cells and in certain lung cancer lines that retain extensive GJIC.